Penyuluhan Jamu Aman untuk Meningkatkan Pengetahuan Siswa di MTs GUPPI Wanareja - Salasanti, Citra Dewi; Yusuf, Fitra Arif Maulana; Nurgifani, Siska; Komara, Yusup; Rahmasari, Melinda; Salsabila, Firyal (Universitas Mataram, 2024)
Jamu is one of the traditional medicines in the form of concoctions or mixtures of ingredients that are processed using traditional processes and used as medicine for generations. According to Riskesdas data for 2010, 60% of Indonesia's population uses herbal medicine. However, several herbal medicines on the market are known to contain a mixture of medicinal chemicals which have a negative impact on health. The purpose of this study was to increase the knowledge of MTs GUPPI Wanareja students about herbal medicine that is safe for consumption. This research is descriptive in nature, respondents were given a pretest questionnaire, material presentation, and posttest evaluation. The results showed that the respondents' knowledge increased by 50.32%, and there was a significant difference between before and after the presentation of the material with a significance value of 0.000 (p <0.05)